US-Iran Tensions and Instability in Iraq: Role of the Popular Mobilisation Units - Fatima Raza (Strategic Studies, 2021)
Popular Mobilisation Units (PMU) is the largest umbrella organisation in Iraq encompassing more than 40 of these paramilitary forces with many of them having deep ties with Iran. Recent killing of the PMU leader Abu Mahdi al Muhandis along with his ally, the Iranian General Qassem Soleimani in a US drone strike concurred a huge loss for Iran and the PMU who had long enjoyed cooperation and influence within Iraq. The PMU, in the absence of its trusted leadership; is predicted to fall apart from within causing instability in Iraq which has been brought about by reckless war-mongering between the US and Iran. This research explores the strategic culture, structure and the role of PMU in bringing about stability in Iraq in the backdrop of continuous deteriorating Iran-US relations. This research argues that in order to make the PMU effective in cultivating peace in Iraq; it would be wise for important stakeholders like Iran and the US to understand its strategic culture and formulate their respective Iraq policies accordingly.